A sense of control : virtual communities for people with mobility impairments - Tilley, Christine (Chandos information professional series., 2009)
This work develops a theoretical framework for a virtual community for people with long-term, severe mobility disabilities. It proposes strategies for implementing a virtual community model based on user information needs. The central theme to emerge from their narratives is how the use of information and communications technology (ICT) allows them to regain a sense of control. The conclusion is that the technology provides strategies for independence and facilitates self-empowerment.